All-Optical Methods to Study Neuronal Function - Papagiakoumou, Eirini (Neuromethods, 2023)
This open access volume provides an overview of the latest methods used to study neuronal function with all-optical experimental approaches, where light is used for both stimulation and monitoring of neuronal activity. The chapters in this book cover topics over a broad range, from fundamental background information in both physiology and optics in the context of all-optical neurophysiology experiments, to the design principles and hardware implementation of optical methods used for photoactivation and imaging. In the Neuromethods series style, chapters include the kind of detail and key advice from the specialists needed to get successful results in your laboratory. Comprehensive and cutting-edge, All-Optical Methods to Study Neuronal Function is a valuable resource for researchers in various disciplines such as physics, engineering, and neuroscience. This book will serve as a guide to establish useful references for groups starting out in this field, and provide insight on the optical systems, actuators, and sensors. This is an open access book.